Pemanfaatan Jahe (Zingiber Officinale) sebagai Upaya Pendukung Penanganan Infeksi Saluran Pernafasan Akut - Lestari, Dian Puspita; Juniansah, Rio; Kusuma, Rahma Rara; Trsinawati, Vivi; Juniarti, Mersa (Jurnal Dehasen Untuk Negeri, 2026)
Acute Respiratory Tract Infection (ARI) is one of the public health problems that is still commonly found in Indonesia. This disease often occurs due to weather changes, unhealthy environmental conditions, and low immune system resistance. One of the efforts that can be made to prevent and support the management of ARI is the utilization of family medicinal plants (TOGA). Ginger (Zingiber officinale) is a herbal plant that is easily found and contains active compounds that are beneficial for respiratory health. This community service activity aims to increase community knowledge and skills in utilizing ginger as a herbal beverage to support the prevention and management of ARI. The methods used include health education, education on the utilization of ginger, demonstrations on the preparation of ginger drinks, and interactive discussions. The results of the activity showed an increase in community understanding of the benefits of ginger as well as greater awareness in utilizing natural ingredients to maintain health.